136 Same-day admission facilitated by a nurse led pathway reduces hospital length of stay for transfemoral transcatheter aortic valve implantation. (May 2019) - MCCALMONT, Gemma; Williams, Paul; Muir, Douglas; Bawamia, Bilal; Arshad, Muhammad
Abstract : Background: There is a growing interest in reducing the hospital length of stay for patients undergoing transcatheter aortic valve intervention (TAVI), with particular focus on patients who are suitable for a transfemoral approach under local anaesthesia. Early discharge has been shown to be safe for a select patient population. However same day admission for TAVI will also influence hospital length of stay and there are few data on the feasibility and safety of this approach. Methods: A same day admission programme was commenced in our unit in April 2017, supported by the introduction of a TAVI Specialist Nurse. We performed a retrospective, single-centre audit to compare the patients treated under the same day admission programme (same day group) with a control group who were admitted the day before their procedure (standard care group) over 12 months period preceding the new programme. Length of stay, baseline and procedural characteristics (table 1 ), and in hospital and 30-day follow-up outcomes (table 2 ) were analysed. Electronic data and medical records were used to collect data on demographics, baseline characteristics, procedural details, hospital outcome and long-term outcome. Results: A total of 77 patients in the standard care group and 102 patients in the same day group were analysed. In the same day group, same day admission was planned in 97 patients (95%) and was successful in 91 (94%) patients. The incidence of same day cancellation was lower in the same day group (11% vs 2%). TAVI was performed successfully in 89 (98%) patients in the same day group and 77(100%) in the standard care group. The median length of stay in the same day group was lower (1 vs 2; p<0.005) than that of the control group, there was no difference in mortality, procedural complications or re-admission rates. Baseline demographics were reported by using descriptive analysis while comparative analysis was used to test the association of different variables. Conclusion: Routine same day admission for TAVI can be safely implemented for patients undergoing transfemoral TAVI with the support of a Specialist Nurse. This led to a shorter length of hospital stay with no detrimental effect on procedure outcomes or readmission rate and has the potential of significant cost savings. Conflict of Interest: no